THE QUALITY OF LEARNING SKILLS IN PRIMARY STUDENTS AND WAYS TO IMPROVE THEM (Multidisciplinary Journal of Science and Technology, 2025)
This article presents theoretical information about the analysis of literary genres in the study of pedagogical and psychological features of the formation of image perception skills in primary school students.